Konstruksi Aspek dan Indikator Karakter Anak Sholeh di Jenjang Sekolah Dasar - Arie Rakhmat Riyadi (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The hope of parents to educate, including sending their children to school, especially for a Muslim, is to have pious (sholeh) children. The character of the pious child generally not yet comprehensive, because only focus on religious elements. This research aims to obtain a complete construct, starting from aspects to indicators of the character at the elementary school level. This research method uses Delphi with a combined approach between qualitative and quantitative. The object of this study is the construct of pious children, which developed through a literature review; In contrast, the subjects of this study were 20 experts from various elements. Qualitative data analysis used in the descriptive analysis section comes from the experts' responses. Quantitative data analysis involves statistical measures ranging from the average, standard deviation, and interquartile range, ending with empirical construct testing through the evaluation of measurement models to see Exploratory Factor Analysis (EFA) using Smart PLS 3.0 software, and assessment of the goodness of fit. The results of this study are the constructs of pious children, which consist of five aspects with a total of 22 indicators spread across each aspect, starting from jismiyah, fikriyah, qolbiyah, amaliyah, and maslakiyah.